Optimization of Restorative Justice in Handling the Crime of Ordinary Theft at the Tuban Police Satreskrim Criminal Unit - Sugiyarno, Kautsar Marchel Toar (Indonesian Journal of Police Studies, 2024)
Restorative Justice is an alternative approach to law enforcement that emphasizes restoring the welfare of victims and perpetrators. This approach emphasizes reconciliation and rehabilitation, not just criminal punishment. Not all criminal acts can be resolved through restorative justice. Only criminal acts that meet the formal and material requirements can be resolved using restorative justice. Ordinary theft is a criminal offense that meets the requirements for restorative justice resolution. The implementation of resolving ordinary theft crimes with Restorative Justice at the Tuban Police is not yet optimal because the number of settlements is very small compared to the number of reported cases of ordinary theft. In this research, the author uses management theory as well as SWOT theory and the concept of optimization, the Restorative Justice concept, the investigator concept, and the concept of ordinary theft to carry out analysis on the research focus. From the research that has been carried out, the results show that the implementation of resolving ordinary theft crimes with Restorative Justice has referred to Perpol no. 8 of 2021 and can be proven by the conformity of implementation in the field with the SOP stated in Perpol no. 8 of 2021. However, the obstacles faced There are only a few Satreskrim personnel who have carried out investigator certification. Apart from that, the DIPA budget obtained by Satreskrim is not yet commensurate with the number of criminal acts, especially ordinary theft crimes. Therefore, the author suggests to the Criminal Investigation Unit to submit their members to the Head of Human Resources to carry out investigator certification.